2019
DOI: 10.3368/le.95.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: Stated versus Revealed Donations and the Differential Role of Behavioral Factors

Abstract: This paper uses a contingent valuation study and an actual donation request to assess the impact of behavioral factors on hypothetical bias in stated willingness-to-pay estimates. Our findings indicate that both the number of respondents willing to donate and the amount they are willing to donate differ substantially between treatments. Behavioral factors play a substantial and significant role; in particular, the extent of warm glow derived from giving and expectations about other people's behavior increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…While several studies show that cheap talk scripts can mitigate or reduce hypothetical bias (Cummings & Taylor, 1999; Murphy, Stevens, & Weatherhead, 2005; Silva et al., 2011), its effectiveness ranges greatly across individuals and contexts. Our results are in line with a growing body of research that reports no difference between valuations elicited in hypothetical and cheap talk scenarios (Brummett et al., 2007; Blumenschein et al., 2008; Bouma & Koetse, 2019) or that finds cheap talk to be generally ineffective, except for certain limited cases (Ami et al., 2011; Barrage & Lee, 2010; Champ et al., 2009; Howard et al., 2017; List, 2001; Moser et al., 2014; Murphy, Stevens, & Weatherhead, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While several studies show that cheap talk scripts can mitigate or reduce hypothetical bias (Cummings & Taylor, 1999; Murphy, Stevens, & Weatherhead, 2005; Silva et al., 2011), its effectiveness ranges greatly across individuals and contexts. Our results are in line with a growing body of research that reports no difference between valuations elicited in hypothetical and cheap talk scenarios (Brummett et al., 2007; Blumenschein et al., 2008; Bouma & Koetse, 2019) or that finds cheap talk to be generally ineffective, except for certain limited cases (Ami et al., 2011; Barrage & Lee, 2010; Champ et al., 2009; Howard et al., 2017; List, 2001; Moser et al., 2014; Murphy, Stevens, & Weatherhead, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Cheap talk is frequently used in stated preference studies but the evidence for its effectiveness in eliciting accurate valuations in line with the true preferences of survey respondents is mixed (Johnston et al., 2017; Penn & Hu, 2019). The strategy continues to receive considerable attention in stated preference research (Bouma & Koetse, 2019; Gschwandtner & Burton, 2020; Howard et al., 2017). In our analysis, we use a shorter version of a cheap talk script that incorporates the primary elements laid out by Cummings and Taylor (1999), similar to that of Aadland and Caplan (2006) and Bouma and Koetse (2019).…”
Section: Survey Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Carpenter (2018) finds the self-reported altruism measures used in the literature to have varying predictive power. Although several studies have verified that self-reported altruism is an important determinant of WTP in CV studies (Nunes and Schokkaert 2003;Clark and Friesen 2008;Nunes et al 2009;Nielsen and Kjaer 2011;Kotchen 2015;Ma and Burton 2016;Bouma and Koetse 2019), all former studies of altruism, to our knowledge, use Likert scale survey statements in their attempts to capture aspects of altruism. 9 Such altruistic statements may capture certain altruistic preferences (Hartmann et al 2017), but the measures could be biased and blurred by idealised personality bias 10 or social desirability bias (Carpenter 2002).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…4 We argue that if people receive a warm glow when stating WTP taxes in the CV survey context, while they do not receive a corresponding warm glow when in fact paying the taxes, CV estimates might be biased. 5 Since altruism is an essential factor when explaining substantial non-use values (Bouma and Koetse 2019), altruism is also important for policy decisions based on cost-benefit analyses that use CV estimates. Research to date has analysed the effect of (stated) altruism on WTP and hypothetical bias, focusing on the validity and reliability of the WTP measure, while the validity of the self-reported altruism measures applied has not been investigated in CV studies to our knowledge.…”
Section: Introductionmentioning
confidence: 99%